Deformacja plastyczna wokół osiowo-symetrycznej szczeliny przedstawionej modelem Dugdale'a - OLESIAK, Zbigniew; WNUK, Miłosz (Engineering Transactions, 1966)
Plastic strain around an axially symmetric crack represented by the Dugdale modelThe introduction contains a brief discussion of a number of works of other authors concerning non-propagating cracks. Next, the method for determining the plastic region (according to Dugdale) is described in the case of the two-dimensional problem. The subsequent part of the paper is devoted to the determination of the range of plastic strain for an axially symmetric crack in a perfect elastic-plastic body.The paper contains a table of the extent of plastic zone in function of the load and a diagram confronting the curves of the distributions of plastic strain zones computed by means of four formulae.